1972
DOI: 10.1139/p72-073
|View full text |Cite
|
Sign up to set email alerts
|

Response Time of the Magnetosphere to the Interplanetary Electric Field

Abstract: Data from the IMP-I satellite are used to determine the lag time between the response of the index of geomagnetic activity AE to fluctuations in the azimuthal component of the interplanetary electric field as measured in the solar ecliptic coordinate system. The lag time is found to lie in the range 30-50 min. The magnitude of the lag time is related to the average energy content of the magnetosphere.On utilise des donnees provenant du satellite IMP-I pour determiner le delai entrela rCponse de I'indice d'acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…In each case, the sharp onsetsof the auroral-zone negative bay and the low-latitude disturbance coincided to within ten minutes. Designating a time midway between the two onsets as To, and identifying this time as the beginning of the expansion phase of an isolated large-scale substorm, Foster et al then It is readily apparent in Figure 1 that the result of a cross-correlational analysis performed between the AE and B z curves would result in a peak correlation at an approximate AE lag of 40 minutes, a time consistent with the results of Meng et al (1973) and Rostoker et al (1972).. However, in the analysis by Foster et al there is little of the ambiguity noted by Meng et al (1973) concerning the meaning of the lag between the B. and AE variations.…”
Section: The Interplanetary Magnetic Field and Magnetospheric Convectionmentioning
confidence: 60%
See 1 more Smart Citation
“…In each case, the sharp onsetsof the auroral-zone negative bay and the low-latitude disturbance coincided to within ten minutes. Designating a time midway between the two onsets as To, and identifying this time as the beginning of the expansion phase of an isolated large-scale substorm, Foster et al then It is readily apparent in Figure 1 that the result of a cross-correlational analysis performed between the AE and B z curves would result in a peak correlation at an approximate AE lag of 40 minutes, a time consistent with the results of Meng et al (1973) and Rostoker et al (1972).. However, in the analysis by Foster et al there is little of the ambiguity noted by Meng et al (1973) concerning the meaning of the lag between the B. and AE variations.…”
Section: The Interplanetary Magnetic Field and Magnetospheric Convectionmentioning
confidence: 60%
“…Finally, information on the time-scale of the magnetospheric response to IMF fluctuations has been obtained in the cross-correlation studies of Arnoldy (1971), Kokubun (1972), Rostoker et al (1972), and Meng et al (1973), which have established that the growth and decay of the AE index follow variations in the interplanetary B z component with a time delay of about 40 minutes. An unambiguous interpretation of this time delay cannot, however, be reached from these studies since intervals of multiple substorms were included.…”
Section: The Interplanetary Magnetic Field and Magnetospheric Convectionmentioning
confidence: 99%
“…The time difference between the southward turning and the geomagnetic disturbances have been studied quantitatively by several authors in different way. ARNOLDY (1971), ROSTOKER et al (1972) and MEND et al (1973) obtained consistent results of 40 min or 1 hr by means of the cross-correlation analysis, but the results were interpreted in different manners. ROSTOKER et al (1972) suggested that the delay is governed by the amount of energy stored in the magnetosphere.…”
Section: Introductionmentioning
confidence: 89%
“…ARNOLDY (1971), ROSTOKER et al (1972) and MEND et al (1973) obtained consistent results of 40 min or 1 hr by means of the cross-correlation analysis, but the results were interpreted in different manners. ROSTOKER et al (1972) suggested that the delay is governed by the amount of energy stored in the magnetosphere. MEND et al (1973) interpreted the time delay to be primarily caused by a difference in the durations of the negative Bz event and the substorm magnetic bay event, and not to reflect the difference in the times of the substorm onset and the southward turning of the IMF.…”
Section: Introductionmentioning
confidence: 89%
“…It is thus natural to correlate magnetospheric behavior with conditions measured in the solar wind and IMF. A number of solar wind–magnetosphere coupling functions have been postulated for the dependence of energy input to the magnetosphere on interplanetary parameters [e.g., Rostoker et al , 1972; Maezawa , 1979; Murayama , 1982; Baker , 1986; Liou et al , 1998].…”
Section: Introductionmentioning
confidence: 99%